2004
DOI: 10.1080/14680629.2004.9689975
|View full text |Cite
|
Sign up to set email alerts
|

Rutting and Moisture Resistance of Asphalt Mixtures Containing Polymer and Polyphosphoric Acid Modified Bitumen

Abstract: Initial engineering properties of materials as well as mechanical and environmental conditions governs the behaviour of asphalt pavements in service. To enable pavements to accommodate increasing traffic intensity and axle loads in varying climate environments, high quality bitumen is required. Special binders are also needed for other applications, such as bridges and airport runways. These examples suggest the necessity of bitumen modification. While modification of bitumen may be carried out via other metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…Among the different acids that can be used to improve bitumen properties through chemical modification, polyphosphoric acid (PPA) has been studied in numerous papers and patent publications [172][173][174][175][176][177][178][179][180][181][182][183][184][185]. From a chemical point of view PPA is an oligomer of phosphoric acid (H 3 PO 4 ), with no free water, which may have more than 10 repeating units [122].…”
Section: Ppa-based Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the different acids that can be used to improve bitumen properties through chemical modification, polyphosphoric acid (PPA) has been studied in numerous papers and patent publications [172][173][174][175][176][177][178][179][180][181][182][183][184][185]. From a chemical point of view PPA is an oligomer of phosphoric acid (H 3 PO 4 ), with no free water, which may have more than 10 repeating units [122].…”
Section: Ppa-based Techniquesmentioning
confidence: 99%
“…A more detailed description can be found in [4,122,186]. From a thermal and rheological point of view bitumen/PPA blends [185][186][187][188] have shown an increased high-temperature performance with no significant changes in the low-temperature ones. It has been also found that PPA can improve the storage stability of PmBs.…”
Section: Ppa-based Techniquesmentioning
confidence: 99%
“…Although the hydrophilic nature of PPA challenges the moisture resistance of bitumen modified with PPA, there are studies indicating that the addition of PPA to bitumen results in mixes with less sensitivity to moisture damage. 6 Our recent studies have also confirmed the improved moisture resistance of bitumen-containing PPA, though the duration of the improvement is short. In terms of different dosages of PPA, Hossain et al showed that higher amounts of PPA make asphalt binders more susceptible to moisture damage.…”
Section: ■ Introductionmentioning
confidence: 56%
“…Moreover, PPAmodified bitumen has been shown to have better lowtemperature properties compared to air-blown bitumen. 6 Despite PPA's acidic nature, the antioxidative characteristic of PPA causes improved resistance to aging for PPA-modified bitumen. 5 The improved aging resistance of PPA-modified bitumen was also noted by De Filippis et al 7 H-NMR results confirm the oxidation stability of PPA-modified bitumen; this is evidenced by a decrease in the content of α-H after PPA modification, since these H atoms are associated with susceptibility to oxidation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Lately, PPA-modified bitumen has been used in significant volumes in roadway construction to increase bitumen viscosity and reduce its deformation in summer temperatures under repeated traffic load. 1 The PPA-induced chemical reaction(s) that lead to the increase in bitumen viscosity have been the subject of some work, [2][3][4] but the complexity of bitumen composition does not lend itself easily to the investigation of detailed chemical reactions. Consequently, we have used bitumen model compounds to investigate the possible reactions between bitumen and PPA.…”
Section: Introductionmentioning
confidence: 99%